2020
DOI: 10.9734/jamb/2020/v20i830274
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in Combination with Antifungals to Combat Drug Resistant Candida – A Concept on Drug Repurposing

Abstract: Candida spp. are emerging pathogens of hospital-acquired infections that causes invasive candidiasis, leading to human mortality and morbidity. Evolution of resistance to different groups of antifungal drugs is a major concern nowadays. Resistance mechanism in some of the antifungal drugs are formation of biofilms, alterations in drug target and lowered intracellular drug levels caused by efflux pumps. Introduction of novel strategies are necessitous to eliminate the phenomenon of drug resistance.  Drug repurp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, recent studies in the United States, Europe, and Asia have shown increased resistance of Candida species to fluconazole and echinocandins [ 5 , 11 ]. Due to the limitations of antifungal agents and the development of antifungal resistance, combination therapy can be an effective strategy for the therapeutic challenges of candidiasis caused by resistant species [ 21 ]. Studies of antifungal drugs with different mechanisms of action against Candida species have also been performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies in the United States, Europe, and Asia have shown increased resistance of Candida species to fluconazole and echinocandins [ 5 , 11 ]. Due to the limitations of antifungal agents and the development of antifungal resistance, combination therapy can be an effective strategy for the therapeutic challenges of candidiasis caused by resistant species [ 21 ]. Studies of antifungal drugs with different mechanisms of action against Candida species have also been performed.…”
Section: Discussionmentioning
confidence: 99%